Applicability of high-pressure direct-injected methane jet for a pure compression-ignition engine operation. (1st September 2019) - Lee, Tae Kyung; Park, Hyunho; Hyun, Jaewoo; Lee, Changhyun; Song, Han Ho
Highlights: Compression ignition operation of pure methane jet with intake heating ∼400 °C at a compression ratio of 15.5. Direct injection of methane with GDI injector at 200–400 bar. Experiments by varying the engine load, injection timing, and injection pressure. Results of engine performance and emissions, and comparison with conventional diesel fuel. Abstract: Natural gas has been suggested as an alternative fuel for compression ignition (CI) engines because it generates significantly less pollutants and has a smaller carbon footprint, while maintaining the cycle efficiency. However, the high auto-ignition temperature of natural gas typically requires the use of a quasi-compression ignition method such as homogenous charge compression ignition (HCCI) or a dual-fuel mode. Yet, methods such as these are unable to realize the full potential of high efficiency and low emissions. This motivated us to evaluate the applicability of a high-pressure direct-injected natural gas jet for a pure CI engine under various engine load, injection timing, and injection pressure conditions using a single cylinder CI engine with a compression ratio of 15.5. The intake temperature was raised to 400 °C to achieve the auto-ignition temperature of methane after compression and a multi-hole GDI injector capable of operating at a pressure of 400 bar was used for fuel injection. As a result, CI operation was possible, but ignition occurred after the end of the injection in the form of a partially premixed flame rather than a diffusion flame for all conditions under which the engine was operated. A sufficient equivalence ratio of 0.8 was achieved at an injection pressure of 300 bar and injection duration of 1.6 ms with the multi-hole GDI injector, and the GMEP value varied from 2 bar to 5.5 bar according to the equivalence ratio. However, at an equivalence ratio of 0.7 or higher, the combustion efficiency decreased drastically because of the limit of the volume fraction of the piston bowl at TDC and the narrow nozzle distribution of the GDI injector. Measurement of the pollutants indicated that the total number of particles from methane CI operation exceeded that of diesel at an equivalence ratio of 0.74 in the same engine setup because of incomplete combustion; however, the total mass of the particulate matter (PM) was approximately 15% of the diesel because the average particle size from methane CI was approximately one third smaller than that of diesel. However, the high post-compression temperature for the auto-ignition of methane gas resulted in a high peak temperature, which resulted in the production of approximately 2000 ppm NOx under all test conditions. The results of the parametric study showed that, as the injection timing retarded, the ignition timing was almost equally retarded, thus the combustion was still observed in the form of a diffusion flame. As the injection pressure increased, the ignition delay became shorter and the emission of PM could be further reduced, but the NOx emission increased.